Analisis Kebijakan Penarikan Retribusi Pariwisata (Studi Implementasi Perda Nomor 27 Tahun 2002 tentang Retribusi Tempat Rekreasi dan Pariwisata di Kabupaten Trenggalek) - H.M. Ismail (Jurnal Aplikasi Manajemen, 2012)
Trenggalek as an autonomous region is an area that has the right and authority to manage their own household as well as the District elsewhere in Indonesia. To manage the household, the city is requiring funds. In this regard, the Local Government Trenggalek pursuant to Act No. 25 of 1999 given the financial resources to finance their activities for among others derived from: (1) Revenue (PAD), (2) For the results: ( 3) Public Subsidies, (4) Special Subsidy; (5) Loans, (6) and the acceptance of others are legal. This study takes place at the Department of Youth, Sport, Tourism and Culture (DISPORAPARIBUD) Trenggalek with research sites Guo Lowo Area Sightseeing in District Watulimo Trenggalek. The approach used is qualitative with the type of qualitative descriptive study. Data collection techniques were interviews, documentation, and observation. The study found three main results, namely: (1) Collection of levies into the area of tourism is one of several types of collecting user charges in government Trenggalek. Collection of levy is a form of implementation of government policy in the form Trenggalek Trenggalek District Regulation No. 27 of 2002 and No. 14 of 2008 which aims to set the order, smoothness and comfort of visitors, in addition to improve the original income Trenggalek, (2) Factors supporting in the implementation and management of levies into the Area Tourism Guo Lowo in District Watulimo Trenggalek the availability of facilities and infrastructure that exist today can be utilized optimally to deliver services to the compulsory levy, coordination with relevant agencies, good supervision and support from the communities around the region tourism, particularly tourism service providers, (3) Obstacles faced in implementation of the levy collection in the field is the lack of other infrastructure facilities, lack of personnel, the number of access road in to the area of tourism as well as residential areas and the lack of publications on a regional scale, national, and international.Keywords: levy, tourism, local regulations